To solve the equation \( 2 \cdot (x - 3) = 0 \) using the Zero Product Property, we follow these steps:
-
Identify the product: The equation is already in the form of a product equal to zero. The product is \( 2 \) and \( (x - 3) \).
-
Set the product to zero: According to the Zero Product Property, if the product of two factors is zero, then at least one of the factors must be zero. Since \( 2 \) is a constant and not equal to zero, we focus on the other factor:
\[ (x - 3) = 0 \]
-
Solve for \( x \): Now, we can solve the equation \( x - 3 = 0 \):
\[ x - 3 = 0 \implies x = 3 \]
Thus, the value of \( x \) that makes the statement true is \( \boxed{3} \).